A theoretical underpinning of the pesticide Groundwater Ubiquity Score (GUS) - Steenhuis Tammo S.; Brindt Naaran; Pacenka Steven; Richards Brian K.; Parlange J.-Yves; Hassanpour Bahareh (Journal of Hydrology and Hydromechanics, 2024)
The Groundwater Ubiquity Score (GUS) is widely used to indicate the relative leachability of pesticides based on the soil half-life and the adsorption partition coefficient. In this manuscript, we derive mathematically the Theoretical Groundwater Ubiquity Score (TGUS) that, based on considerations of the preferential movement of pesticides to groundwater and a first-order pesticide degradation model, leads to a similar function as the GUS model. In the preferential flow model, movement to groundwater is fast, and the adsorption partition coefficient is thus not used for calculating the travel time to the groundwater (as it is in the advective-dispersive equation) but rather only determines the distribution of the pesticide between the water and soil phases. Both the GUS and TGUS models well predict the groundwater contamination of the originally studied pesticides for rainfall event(s) that caused pesticide leaching from 30 days after application. The theoretically derived Groundwater Ubiquity Score (TGUS) shows, in accordance with experimental evidence, that for leaching events shortly after spraying, the mass lost to (and resulting concentration in) groundwater is inversely related to the adsorption partition coefficient and not necessarily to the GUS index.